Distribution of alpha particle tracks on CR-39 detector in radon diffusion chamber. (April 2021) - Stajic, J.M.; Markovic, V.M.; Milenkovic, B.; Stevanovic, N.; Nikezic, D.
Abstract: The aim of this study was to investigate spatial distribution of alpha particle tracks produced by radon and its progeny in radon diffusion chambers. Three cylindrical chambers equipped with CR-39 detectors were used in the experiment. Radon concentration was estimated using RAD7 device. Distribution of alpha particle tracks on detector surface was found to be nonuniform; track density close to the chamber walls was up to 30% lower than in the centre. The results were compared with the predictions of analytical method applied to the same chamber dimensions. Critical angle of detection was expressed in relation to particle incident energy, using TRACK_VISION computer software. It was shown that the shape of track density distribution highly depends on the chamber size, as well as on the critical angle of particle detection. Sources of track density variation were investigated by analyzing partial contributions from volumetric and deposited fractions of radon and its progeny. Side-wall contribution increases while volumetric and plateout contributions decrease with increasing radial distance from detector centre. Changing chamber dimensions affects the relative influences of these partial contributions, resulting in different distributions of visible tracks on detector surface. Experimental results were compared to the values obtained using previously developed software based on Monte Carlo method. Five different expressions of detector response function (V) were applied in the study; two of them significantly underestimated the experimental results. Highlights: Distribution of alpha particle tracks on detector surface is not uniform. Track density distribution exhibits complex dependence on chamber dimensions. Partial contributions from volumetric and deposited fractions were analysed. Critical detection angle was expressed in relation to particle incident energy.